The impacts of growth and inequality on rural poverty in China - Yin Zhang; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper analyzes the evolution of poverty in China from the late 1980s to the late 1990s, employing a version of Shapley decomposition tailored to unit-record household survey data. The changes in poverty trends are attributed to two proximate causes— income growth and shifts in income distribution. Different datasets, poverty lines, poverty measures, and equivalence scales are used to examine the robustness of the results. Potential biases arising from ignoring differential regional prices and inflation are also investigated. Notwithstanding some ambiguities in the results, it is consistently found that rural poverty increased in the second half of the 1990s and adverse distributional changes are the main cause. – poverty ; Shapley decomposition ; unit-record data ; China
Keywords: O15; O53; 330; Ländliche Armut; Einkommensverteilung; China